Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Rayana Outfit - Ria Marlia Hartati; Dadan Abdul Aziz Mubarok (Universitas Persada Indonesia YAI, 2025)
This study aims to analyze the influence of service quality and trust on customer loyalty at Rayana Outfit. The research method used a quantitative approach with a sample of 75 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results show that service quality and trust have a significant positive effect on customer loyalty. Trust has a more dominant influence than service quality. The study recommends that Rayana Outfit improve service quality and implement a more competitive customer trust strategy to increase customer loyalty.